Unraveling the role of innovation platforms in supporting coevolution of innovation: Contributions and tensions in a smallholder dairy-development program - Kilelu, Catherine W.; Klerkx, Laurens; Leeuwis, Cees (International Food Policy Research Institute, 2016)
A number of studies have addressed issues of platform organization, but few have studied how platforms shape innovation processes. Chapter 9 (Kilelu, Klerkx, and Leeuwis) attempts to unravel the role of platforms in supporting innovation, through an in-depth study of a smallholder dairy-development program in Kenya. The findings indicate that innovation processes produce numerous tensions and unexpected effects, and that intermediation and facilitation are crucial for resolving tensions. Innovation platforms require adaptive management that is supported by monitoring for continuous learning.